Using the Yammer cloud service to organize project-based learning methods - Dmytro M. Bodnenko; Halyna A. Kuchakovska; Oleksandra V. Lokaziuk; Volodymyr V. Proshkin; Svitlana H. Lytvynova; Olha H. Naboka (Academy of Cognitive and Natural Sciences, 2022)
The article reveals and interprets the key features of project-based learning based on cloud-based services: social activity; convenient communication in a team during the project implementation and at the resulting stage; open educational space; self-learning and self-improvement; use of interdisciplinary links to combine students of different years of study (1--4 degrees of the first (bachelor's) level and students of the second master's level) to joint research teams to study through research; purposeful motivation of cognitive and research activity of students within the discipline with the use of interdisciplinary connections; formation of digital literacy of students. The advantages and disadvantages of the Yammer cloud service are presented and a comparative analysis of this service with similar cloud services is performed. Examples of using Yammer in professional project activity are given. The stages of using project methods using the small group method are analyzed and detailed: initiation; planning; conducting/implementation; presentation; assessment/defense.